Penerapan Relay Method untuk Meningkatkan Minat Belajar Siswa pada Mata Pelajaran SKI Kelas VII di MTsN 4 Karawang (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
This study aims to improve students’ interest in learning in the subject of Islamic Cultural History (SKI) in class VII B MTsN 4 Karawang through the application of the Relay method. The main problem found is the low interest in learning of students, which causes them to tend to be passive and do not understand the material. By using the Classroom Action Research (CAR) approach carried out in two cycles, this method aims to create a more active and enjoyable learning atmosphere. Students are divided into several groups and take turns answering questions, so that all students are involved and motivated. The results of the study showed a significant increase in interest in learning between the first and second cycles. In the first cycle, the average student interest in learning was at 67.5%, and increased to 88.75% in the second cycle. This proves that the application of the Relay Method is effective in increasing enthusiasm, cooperation, sense of responsibility, and student activity during learning.